Atomic-scale matrix partitioning of polar and antipolar motifs for high-density energy storage capacitors - Dingheng Lin; Bin Kong; Jinjun Liu; Jiarong Lv; Ya Yang; Wei Zhang; Sen Chen; Ning Liu; Zhongbin Pan (Chemical Engineering Journal, 2026)

CRISPR/Cas9-mediated knockout of CsRDL1 decreases the susceptibility of Chilo suppressalis to cyproflanilide - Jungang Zhou; Ziren Zang; Hongshuai Gao; Jinjun Sun; Lina Xu; Qiao Gao; Hualiang He; Wenbing Ding; Lin Qiu; Youzhi Li (Pesticide Biochemistry and Physiology, 2026)

Fluid-like polarization rotation in interpenetrating diffuse phase boundary for dielectric capacitors - Ya Yang; Yawen Cui; Linqiong Xu; Jiarong Lv; Dingheng Lin; Bing Kong; Jinjun Liu; Ning Liu; Zhongbin Pan (Chemical Engineering Journal, 2026)

PPIL1 promotes hepatocellular carcinoma progression and associates with poor prognosis - Yunyu Wu; Shuqing Jiang; Junming Yu; Hechun Lin; Saihua Zhang; Yizi Jin; Yang Su; Wenjiao Jin; Chao Ge; Qin Geng; Taoyang Chen; Jinjun Li; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Performance study of automotive heat pump system with different refrigerants and leakage combustion characteristics of R290 - Kang Li; Lin Wu; Soheil Mohtaram; Yafen Tian; Ni Liu; Hua Zhang; Jinjun Yan; Qize He; Chao Li; Tao Yang (International Journal of Refrigeration, 2025)

Atomically dispersed iron-decorated activated carbon for boosted adsorption of oxygenated/chlorinated volatile organic compounds - Fangda Wei; Haiyan Bai; Xi Cui; Feng Wu; Zhixiong You; Lin Yue; Jinjun Li (Journal of Environmental Chemical Engineering, 2025)

A century of advances in molecular genetics and breeding for sustainable resistance to rice blast disease - Xilai Huang; Wei Yao; Qianru Chen; Jinjun Lin; Jun Huang; Yuying Zou; Chenglong Guo; Bei He; Xiao Yuan; Chengyang Xu; Xionglun Liu; Yinghui Xiao; et al. (Theoretical and Applied Genetics, 2025)

Localized chemical disorder induced superior energy storage performance of PbZrO3-based antiferroelectric ceramics - Mingqi Shi; Xingke Pan; Dingheng Lin; Ning Liu; Wei Zhang; Sen Chen; Peng Li; Jinjun Liu; Hongzhen Xie; Zhongbin Pan (Chemical Engineering Journal, 2025)

Micro-charging and accumulation of shale oil in lamellar shale interbedded with siltstones, Dongying Depression, Bohai Bay Basin - Jinjun Xu; Qilong Wu; Xiangang Cheng; Kaiyue Li; Yiru Zhao; Jie Wei; Fuqi Cheng; Lamei Lin (Marine and Petroleum Geology, 2025)

Upregulation of C1QC as a Mediator of Blood–Brain Barrier Damage in Type 2 Diabetes Mellitus - Cheng Huang; Jiaxing Lin; Lan Chen; Wenzhe Sun; Jinjun Xia; Min Wu (Molecular Neurobiology, 2025)

Main controlling factors evolution on high-quality source rocks development in the Shanan Sag, Bohaibay Basin, NE China: Implication from structure, depositional environment, and organic matter - Jinjun Xu; Juncai Jiang; Deying Wang; Peng Xu; Feilong Wang; Huiyong Li; Xiangang Cheng; Qilong Wu; Fuqi Cheng; Lamei Lin; Yinbo Xu (Journal of Asian Earth Sciences, 2024)

A pH- and enzymatic-responsive nanopesticide to control pea aphids and reduce toxicity for earthworms - Xuqian Zhang; Ying He; Zitong Yuan; Guangmao Shen; Zan Zhang; Jinzhi Niu; Lin He; Jinjun Wang; Kun Qian (Science of The Total Environment, 2023)

Supply reliability-driven joint optimization of maintenance and spare parts inventory in a gas pipeline system - Lin Fan; Huai Su; Enrico Zio; Yuejun Li; Li Zhang; Shiliang Peng; Yuxuan He; Yucheng Hao; Jinjun Zhang (Gas Science and Engineering, 2023)

Supply resilience assessment of natural gas pipeline network systems - Zhaoming Yang; Huai Su; Xingkai Du; Enrico Zio; Qi Xiang; Shiliang Peng; Lin Fan; Michael Havbro Faber; Jinjun Zhang (Journal of Cleaner Production, 2023)

Rule-Based Object-Oriented Water Resource System Simulation Model for Water Allocation - Pengfei Lin; Jinjun You; Hong Gan; Ling Jia (Water Resources Management, 2020)
Simulation is a basic method to analyze water resources system and provide information for decision-making. In this study, a framework is presented that describes the basic elements in a water resource system and a modelling technique integrating conceptual simulation and rule control. To formulate the process of the water cycle and water exploitation with a mathematical model, the water system is described based on adjustable relevant rules and respective parameters with experiences and pragmatic demands in the framework. The rule set describes the principles required to design conceptual networks and control the concrete processes of movement and conversion of different water flows. Combined with object-oriented programming, different calculation functional modules are classified based on the characteristics of water source layers, and the processes that occur in the networks are realised in the computation. The influence of the South-to-North Water Diversion project on the Haihe River basin is analysed by the rule-based object-oriented water resource allocation simulation model. According to the simulation results, groundwater extraction will be reduced by 6,181 million m 3 . The relationship between water source replacement and water layer exchange in the Haihe River basin is analysed, and the feasibility of the model is verified. Based on the rule-based model, the user requirements can be taken into account conveniently, and the rules are flexible to adjust with experiences and real conditions. This model can be used to simulate complex water resource systems.

Exploring the vertical accretion of ornithogenic sediments from the Xisha Islands, South China Sea, by seabird subfossils - Liqiang Xu; Jinjun Zhao; Libin Wu; Lin Chen; Xiaodong Liu (Journal of Quaternary Science, 2018)
Reef islands of the Xisha Islands, South China Sea, were formed during the mid–late Holocene. However, the vertical accretion of ornithogenic sediments of the islands is not well understood owing to a lack of precise dating. Here we present an analysis of seven of the Xisha Islands, and reconstruct their accumulation history based on radiocarbon analysis of seabird subfossils. From Clam‐based age–depth models, a universal development mode of the Xisha Islands is hypothesized. The mean accumulation rate of guano sediments on the Xisha Islands in the late Holocene was 1.02 ± 0.42 mm a −1 . The sum of the deposition rate of coral sands and the rate of ornithogenic accumulation is lower than or close to the current rate of sea level rise in the Xisha Islands, implying a potential threat to the islands’ safety. This study also provides robust evidence for a sequence of island development associated with seabirds.

Histopathological changes in zebrafish embryos exposed to DLPCBs extract from Zhanjiang coastal sediment - Yunpeng Yu; Fanghong Nie; Anthony Hay; Hongying Lin; Yi Ma; Xianghong Ju; Dongliang Gong; Jinjun Chen; Ravi Gooneratne (Environmental Monitoring and Assessment, 2017)

GTPase activity is not essential for the interferon-inducible MxA protein to inhibit the replication of hepatitis B virus - Zhijian Yu; Zhanhui Wang; Jinjun Chen; Hui Li; Zhanzhou Lin; Fan Zhang; Yuanping Zhou; Jinlin Hou (Archives of Virology, 2008)